A Mannosylated, PEGylated Albumin as a Drug Delivery System for the Treatment of Cancer Stroma Cells. (4th August 2021) - Mizuta, Yuki; Maeda, Hitoshi; Ishima, Yu; Minayoshi, Yuki; Ichimizu, Shota; Kinoshita, Ryo; Fujita, Issei; Kai, Takuma; Hirata, Kenshiro; Nakamura, Teruya; Saruwatari, Junji; Arima, Hidetoshi; et al.
Abstract: Mannose receptors that are expressed on macrophages and fibroblasts in cancer stroma are promising therapeutic targets for cancer treatment. Albumin can be used as a drug carrier in chemotherapeutics due to its accumulation in the tumor tissue by the enhanced permeability and retention effects. A mannosylated albumin was recently developed as a new drug carrier targeting cells that express mannose receptors such as macrophages and fibroblasts in cancer stroma. The mannosylated albumin is specifically distributed to hepatic macrophages in vivo, leading to an extremely short residence time in the blood. Here, a dual‐modified albumin, i.e., mannosylated and polyethylene glycosylated (PEGylated) is reported, to improve its blood circulating time and stromal cell targeting. The product efficiently delivers paclitaxel to stromal cells in a mouse melanoma model, thus resulting in the disruption of stromal cells and suppressed tumor growth, which is seven times stronger than that for PEGylated albumin. The findings suggest that the dual‐modified albumin has the potential to provide maximal therapeutic efficacies of chemotherapeutics for the treatment of intractable cancer. Abstract : A dual‐modified albumin is reported, i.e., mannosylated and polyethylene glycosylated, to improve its blood circulating time and stromal cell targeting. The product efficiently delivers paclitaxel to stromal cells in a mouse melanoma model, thus resulting in the disruption of stromal cells and suppressed tumor growth. The findings suggest that the dual‐modified albumin has the potential to provide maximal therapeutic efficacies of chemotherapeutics for the treatment of intractable cancer.